Mempertahankan Integritas Moral:Etika Kristen dalam Pendidikan Agama di Era Digital - Zamasi, Sozanolo; Paparang, Stenly Reinal; Sirait, Rajiman Andrianus (JURNAL LUXNOS, 2024)
Abstract: The digital era heralds a phenomenon of information and communication technology development where aspects of human life can be publicised, including the context of religion, moral values, ethics, and education. This is considered important because it has the potential to produce something useful, ready to face the challenges and dynamics that continue to grow. The use of digital is certainly not free from its negative influences, including ethics and morality. Although it brings benefits, this era also presents challenges, such as the digital divide and information security. This article highlights the importance of Christian religious education in shaping individual character and morality as well as maintaining moral integrity amidst the ever-evolving digital information flow. In the context of Christian ethics, this study emphasises the need for relevant and responsive religious education to address digital dynamics while maintaining Christian values. Through a descriptive approach, this paper analyses the impact of the digital era on education and explains the foundation of Christian ethics in guiding learners' morality. The results show that Christian religious education remains a relevant force in shaping moral character in this digital age through ethical discussions using collaborative platforms, the significance of implementing digital ethics in the religious education curriculum, and the act of analysing big data to respond to the moral challenges of the digital age.